1960´s seaquake, human sacrifice and reestablishment of balance in Wallmapu - Leiva Salamanca, Ronny Alejandro (2013)
The sacrifice of the mapuche boy José Painecur in the event of the 1960´s seaquake is analyzed related to the mapuche culture vision about the death and the own law exercise, in a context of interculturality and of colonization from the chilean occidental society. The perceptions of the press, the judicial system, social sciences, and the mapuche agents about the case of sacrifice, are presented in an multiple overview in order to show a distinction between the mapuche culture and the chilean occidental culture, especially in the principles of balance and reciprocity with nature, the origin of mapuche own law in it and the function of their own cultural agents in the political and spiritual fields. From this last version, the case is presented by the authors as a transcendental action of reestablishment of balance of the mapuche world.